STRATEGI PENINGKATAN RETRIBUSI PASAR MONCOBALANG KECAMATAN BAROMBONG DALAM PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN GOWA - Sari, Rezha Guspiana; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the strategy for increasing Moncolang Market retribution in Barombong Sub-District in increasing local revenue of Gowa Regency. The type of research used is qualitative research. The results of the research are 1) Intensification through supervision of all activities aimed at the target so that the goals set can be achieved. a) Supervision of market retribution collection. b) The Moncobalang Market Retribution Revenue Target refers to its annual target c) The Implementation of Retribution Collection visits directly to the levy payers. d), work standards are made for retribution collectors so that they are more regular in billing time. e) Moncobalang market facilities and infrastructure provided by the government such as stalls to rest. 2) Extensification takes into account the potential for each levy receipt. a) Adding a place or land b) Cooperation with agencies in the form of cooperation in retribution is going well. c) The facilities and infrastructure needed in selling each are privately owned. d) Increasing levy income, namely by realizing good service.